PEMBERDAYAAN KELOMPOK IBU-IBU MELALUI MARSANJI OLEH MAHASISWA KKN SEBAGAI BENTUK PELESTARIAN BUDAYA LOKAL DI DESA HUTA BARU, MANDAILING NATAL - Chandra Ali Hanapiah Lubis; Ade Khadijatul Z. Hrp; Atika Atika; Muarrif Sani; Mislaini Mislaini; Laila Saqila Putri; Ainun Sakiah; Nur Adilah; Aida Rahmi; Mirna Kurnia Tanjung; Rian Azhari Siregar (CV. Denasya Smart Publisher, 2025)
This Community Service Program (KKN) focuses on empowering a group of women in Huta Baru Village, Mandailing Natal Regency, through the implementation of Marsanji, a local tradition rich in religious, cultural, and communal values. Marsanji serves as a medium for spiritual expression within the community as well as a vehicle for strengthening social interaction and cultural identity. The objective of the activity is to increase the active participation of women in the preservation of local culture and to encourage the role of women in maintaining the sustainability of traditional values amid the challenges of modernization. The implementation methods included field observations, interviews with community leaders, socialization on the importance of cultural preservation, training in activity organization skills, and direct assistance in the implementation of Marsanji. The implementation lasted for two months with weekly meetings facilitated by the KKN team and local traditional leaders. The results of the activity showed an increase in the mothers' understanding, enthusiasm, and involvement, both in terms of cultural knowledge and the regular implementation of Marsanji. The observed social impacts included strengthened solidarity, an increased sense of community among residents, and the growth of young people's concern for cultural heritage. In practical terms, this program contributed to the revitalization of local traditions and opened up opportunities for sustainable women's empowerment at the village level. The recommendations include documenting activities, creating preservation guide modules, and forming independent implementation groups as models for replicating culture-based community service programs. Further evaluation is recommended to measure the long-term impact on the local economy, cultural education, and community sustainability. Involve youth and traditional leaders.